The tomb of Ḳen-Amūn at Thebes - Davies, Norman de Garis, 1865-1941, (Metropolitan museum of Art Egyptian Expedition ;)
"Of this book, the text, in an edition of five hundred copies, was printed by the Southworth press, Portland, Maine... Of the plates in both volumes those in line were made and printed by Charles Whittingham and Griggs, London, England: those in color and monochrome collotype by Emery Walker, London, England."